Peranan Media Sosial Instagram Terhadap Interaksi Sosial Antar Siswa SMA Negeri 2 Palopo (Studi Kasus Jurusan IPS kelas XI) - Khicmah, Nurul (UNIVERSITAS NEGERI MAKASSAR, 2018)
Students as part of the community many are using social media for social interaction with other social media user one of these social media Instagram. This research was conducted at SMAN 2 Palopo. This research aims to find out (1). How social interaction students of grade eleventh Social Science Department that is using Instagram. (2) How the role of social media Instagram in social interactions among students grade eleventh Social Science Department SMAN 2 in action. The population in this research is the grade eleventh Social Science Department who use Instagram as much as 103 students, while for the sample about 82 students using the Slovin’s formula. As for the technique of collecting data using the method of observation, things are observed i.e. profile SMAN 2 Palopo and process direct interaction as well as indirect interaction through social media and informer screen capture and then interview i.e., duration which used by students in a day for access Instagram, the role Instagram in social interaction of students, the reason students accesses Instagram and direct interaction during the process of using social media and documentation, be either Instagram content social interaction with social media Instagram. With the consent of the informants, screen-capture to in later analyzed in order to be known to students in Instagram functions interact. While the analysis used in the study is qualitative, descriptive. The results of this research show that most instrumental in Instagram can change student’s behavior. Instagram is more often used to find information related to entertainment. Instagram release as a means for students with poured it in the feature instastory. Postings-postings on Instagram can also make the students sympathize. There are 89% of students say that social media plays a role in their social interaction at school. There are 6% of students who consider Instagram may play a role in their social interactions and 5% who feel not acted.